EVALUATION THE EFFICIENCY OF INPATIENT DRUG DISTRIBUTION IN THE PHARMACY DEPARTEMENT OF TARAKAN HOSPITAL IN CENTRAL JAKARTA - Ika Purwidyaningrum; Lukman Hakim; Sri Wahyuni Pujitami (JURNAL MANAJEMEN DAN PELAYANAN FARMASI (Journal of Management and Pharmacy Practice))
Drug management in Hospital which consist of stages are selection, procurement, distribution and use. Result of preliminary observation done in Pharmacy departement of Tarakan Hospital found some inefficiency problem in distribution steps such as expired and damage control, conformity of record to physical checks on drug management, etc. Therefore, it necessary to evaluation the efficiency rate of inpatient ward drug management distribution. Research design was descriptive, retrospective and concurrent with the evaluation of documents relating to inpatient drug distribution process. The study used a sample of drugs including Class A medicines criteria. Data collected in the form of qualitative and quantitative data from observations of documents and interviews with relevant officers. Data was presented in tabular and textual descriptions. Data evaluation was descriptive using SPSS. Measurement of the efficiency of drug distribution was done by using indicators of the efficiency of Depkes and WHO, then compared with that indicator to determine the existence of inefficiency. The results showed, that according to several indicators inpatient ward drug distribution was not been efficient, inefficiency drug management indicators at this stage of the distribution occurs on a match between the physical card stock while (93.27%).Damaged and / or expired drugs in 2008 was 0.23% in 2009 was 0.48%. Prescriptions are not served in 2008 was 1.52%, 2.28% in 2009. TOR in 2008 was 6 times and in 2008 was 6.9 times. Efficient distribution of drugs already on the length of service time and the availability of prescription drugs Key words: drug distribution, efficiency, Pharmacy departement of Tarakan Hospital